Evaluation of Some Phenotypic, Physiological and Egg Quality Traits of African Black Neck Ostrich under Arid Desert Conditions of Libya - El-Safty, S.; Mahrose, Kh. M. (International Journal of Poultry Science, 2009)
Twenty birds of African Black Neck Ostrich (10 of both males and females) were used in the present study in a completely randomized design to verify and evaluate the differences between males and females of ostrich in some phenotypic and physiological traits, likewise the egg quality traits were estimated under the poor desert conditions of south Libya. The main results of the present study showed that males of ostrich were taller (p<0.01) than females (240.9 vs. 218.0 cm) and had significantly (p<0.05) lower feather length than those of females either in tail or wing feathers. Serum albumin level was higher (p<0.05 and 0.01) in males than females, while the reverse occurred with each of globulin, calcium and magnesium. The poor desert situations of the current study had a pronounced effect on the measurements of both internal and external egg quality. Where, all values of egg quality traits were less than those found by many investigators. Correlation coefficients among the traits that have been studied were significant (p<0.05 and 0.01) varied between negative and positive values in some cases. The highly negative correlation was observed between male height trait and serum albumen, while the converse result was realized with serum globulin trait.